Repeated echocardiography: essential in the management of Staphylococcus aureus endocarditis. Issue 773 (March 1990) - O'Sullivan, J. J.; Aherne, T.; Erwin, J.
Abstract : Staphylococcus aureus endocarditis in a previously healthy 25 year old man is described. Repeated echocardiography recorded rapid progression of aortic root and interventricular septal involvement and, even though the patient was clinically stable, early surgery was advised with a satisfactory outcome. This case report clearly demonstrates the vital role of repeated cross-sectional echocardiography in the management of such cases.